O poder diretivo do empregador e os direitos fundamentais do trabalhador na relação de emprego - Nascimento, Nilson de Oliveira (2008)
This paper deals with the study of the employer's managing power and its various forms of manifestation over the employee's subordination condition within the context of labor relationships. The (employer's) managing power and the (employee's) subordinated labor are intensely related in the daily labor relationships, because such are inherent to the labor agreement itself. Due to such intense interaction between the power of ordering and the duty of respecting, the study of the employer's managing power is justifiable as from a deeper conception, not being limited to the traditional legal methods, but actually capable of facing the interdisciplinary nature of the matter, especially with regards to its constitutional framework, relatively to the possibility of incidence of constitutional and fundamental rights in the individual labor relationships. This paper approaches the subjects of a labor agreement: employee and employer and the legal, doctrinaire and jurisprudential perspectives of such social players, as integral parts of the labor relationship. It further establishes the limits of the employer's managing power, and on the other hand, the employee's subordination duty. In conclusion, this paper promotes an analysis of the constitutional and fundamental rights of workers and the possibility of such rights being incident upon the individual labor relationships. Finally, this paper studies labor agreements and their subjects, the employer's managing power and its means of manifestation and, finally, the constitutional and fundamental rights of the employee as a means of limiting the command power within the context of labor agreements